Risk assessment about effectiveness of biosecurity implementations on horse properties in Turkey - Ince, OB; Paksoy, Y; Sait, A (Journal of the Hellenic Veterinary Medical Society, 2024)
The present study was performed by conducting interviews with 382 horse owners and managers between April 2019 and March 2022 to examine biosecurity implementations on non-commercial horse properties in Turkey and the attitudes and behaviors of horse owners toward viral horse diseases and explain the procedures that visitors should follow. Data were collected with a semi-structured questionnaire. While collecting data from horse owners, 548 nasal swabs were taken from horses on properties to detect equine viral arteritis infection. Correlations between property-level variables and biosecurity implementations in horses were analyzed by logistic regression. Swap samples were investigated for equine arteritis virus antigen by PCR. While 341 (89.27%) of horse owners and managers reported that they applied biosecurity procedures to check the health of newly arrived horses on the property, 125 (32.72%) stated that they applied isolation as a standard procedure upon the entry of horses to the property. On properties where isolation was not routinely applied, the main reason for isolating horses was an illness that emerged on other properties (n=78). Few participants (n=44) checked new horses for fever or other clinical symptoms of infectious disease. Only 54 (14.14%) horse managers reported that they applied visitor procedures. Within the general framework, 301 (78.79%) of horse properties were visited by a horse specialist, but 51 (13.35%) reported the biosecurity procedure for these visits. The obtained findings simplify a better insight of property owners' effective decision-making processes behind horse health discretions and can meet feedback to the sector stakeholders on influential biosecurity implementations.